An analysis of the risk from Xanthomonas campestris pv. musacearum to banana cultivation in Eastern, Central and Southern Africa - Smith, J.J.; Jones, D.R.; Karamura, E.; Blomme, G.; Turyagyenda, F.L. (Bioversity International, Montpellier, France, 2008)
Xanthomonas wilt, which is commonly known in East Africa as banana Xanthomonas wilt (BXW), banana bacterial wilt or enset wilt, is a devastating disease caused by the bacterium Xanthomonas campestris pv. musacearum. It was first reported in 1968 in Ethiopia, where it remained confined until it was observed in Uganda in 2001. The subsequent spread of the bacterium throughout the Great Lakes region, where banana forms a large proportion of the diet, is posing a serious threat to food security. The authors, scientists from the Central Science Laboratory in the UK and Bioversity International in Uganda, discuss the distribution and epidemiology of the causal agent and the measures farmers can use to protect their plants from contracting this deadly disease. They also analyse the impact of the measures deployed to date and make recommendations to reduce the risk of the disease spreading to other countries.
Keywords: policies; integrated pest management; bananas